Using ultrasound tongue imaging to analyse maximum performance tasks in children with Autism: a pilot study. - McKeever, Louise; Cleland, Joanne; Delafield-Butt, Jonathan (Clinical Linguistics & Phonetics, 2022)
This study proposes a protocol for assessing speech motor control in children using maximum performance tasks with simultaneous acoustic and ultrasound recording. The protocol was piloted on eight children with autism spectrum disorders and nine typically developing children. Diadochokinesis rate, accuracy, and consistency were elicited using an imitation paradigm where speakers repeat mono-, bi-, and tri-syllabic stimuli at increasing rates. Both traditional measures of rate, accuracy and consistency and an ultrasound tongue-shape analysis of slow versus fast productions were undertaken. Preliminary results suggest that the protocol is feasible with children with communication disorders. Instrumental measures suggest greater variability in tongue movements in the children with autism that is not detected using perceptual measures of accuracy. A subgroup of children with autism showed some evidence of differences in speech motor control. Ultrasound tongue imaging appears to be a useful method for gaining additional insight into speech motor control.